How and Why Homeless People Are Regulated Differently - Skolnik, Terry (Université d'Ottawa | University of Ottawa, 2018)
Many legal theorists have examined the ways in which homeless people are—and can be—regulated differently than people with homes. Previously applied legal theories have invaluably contributed to understanding how quality-of-life offences disproportionately impact homeless people’s negative freedom or violate their constitutional rights. Despite this, they have certain shortcomings in that they fail to address the harm to homeless people’s freedom from potential interference, rather than just actual interference, and the state’s capacity to enact rules that disproportionately impact those without access to housing. This article argues that the republican theory of freedom (or republicanism) demonstrates how and why quality-of-life offences undermine homeless people’s freedom but does so in ways that address those shortcomings. Applying Philip Pettit’s republican theory of freedom as non-domination, the author argues that existing theoretical accounts, which are concerned with actual interference experienced by homeless people, fail to capture the risk of potential non-egalitarian interference when attempting to lawfully alleviate their needs in private. This risk can lead to homeless people abandoning their preferences, altering their pursuits, or being deferential towards others in order to avoid interference. Consistent with this theory of freedom, the author argues that homeless people who adopt these coping mechanisms to avoid actual interference are not meaningfully free and, furthermore, that the types of non-egalitarian trade-offs that homeless people must make to obey quality-of-life rules suggests that their freedom is undermined in ways ignored by negative freedom and constitutional theories. The author argues that while theorists recognize that quality-of-life offences may disproportionately affect homeless people because they live in public, they rarely address the non-egalitarian implications of the state’s greater capacity to regulate how homeless people alleviate their needs without the privacy of a home. Republicanism thus offers insight into how public authority’s greater capacity to regulate common property and protect its value raises important egalitarianism concerns for those who have no private place to live.
Keywords: homelessness; freedom; public property; domination; republicanism; quality-of-life